Cerebral and Muscle Oxygenation during Repeated Shuttle Run Sprints with Hypoventilation - Woorons, Xavier; Dupuy, Olivier; Mucci, Patrick; Millet, Gregoire P.; Pichon, Aurelien (International Journal of Sports Medicine, 2019)
Ten highly-trained Jiu-Jitsu fighters performed 2 repeated-sprint sessions, each including 2 sets of 8 x ~6 s back-and-forth running sprints on a tatami. One session was carried out with normal breathing (RSN) and the other with voluntary hypoventilation at low lung volume (RSH-VHL). Prefrontal and vastus lateralis muscle oxyhemoglobin ([O2Hb]) and deoxyhemoglobin ([HHb]) were monitored by near-infrared spectroscopy. Arterial oxygen saturation (SpO2), heart rate (HR), gas exchange and maximal blood lactate concentration ([La]max) were also assessed. SpO2 was significantly lower in RSH-VHL than in RSN whereas there was no difference in HR. Muscle oxygenation was not different between conditions during the entire exercise. On the other hand, in RSH-VHL, cerebral oxygenation was significantly lower than in RSN (−6.1±5.4 vs−1.5±6.6 µm). Oxygen uptake was also higher during the recovery periods whereas [La]max tended to be lower in RSH-VHL. The time of the sprints was not different between conditions. This study shows that repeated shuttle-run sprints with VHL has a limited impact on muscle deoxygenation but induces a greater fall in cerebral oxygenation compared with normal breathing conditions. Despite this phenomenon, performance is not impaired, probably because of a higher oxygen uptake during the recovery periods following sprints.
Keywords: hypoxia; NIRS; hypoxemia; combat sports; VHL